2021
DOI: 10.3390/pr9040641
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm to Use Some Specific Lean Manufacturing Methods: Application in an Industrial Production Process

Abstract: Lean Manufacturing includes an ensemble of methods to analyze and continuously improve the functioning of manufacturing systems. The research presented in the literature highlights the fact that these methods are, on their own, in a process of continuous improvement as tools, being used in different ways, for different production systems. The paper presents an algorithm that facilitates the choice of the performance evaluation method, and the choice of the method of improvement that needs to be implemented for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…The ceramics industry is characterized by a very wide range of products and technologies. Based on the literature [4,8,19] and own research [33,34], it can be concluded that the implementation of Lean is best in enterprises with a fixed assortment of production and large production series, e.g., the production of ceramic tiles [32], ceramic blocks or electrical insulators [35]. Against this background, manufacturers of ceramic accessories have a significantly difficult process and implementation industry related to a large range of products produced in small production batches that often change in terms of volume, where the critical point determining the effectiveness of the entire process is the forming stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ceramics industry is characterized by a very wide range of products and technologies. Based on the literature [4,8,19] and own research [33,34], it can be concluded that the implementation of Lean is best in enterprises with a fixed assortment of production and large production series, e.g., the production of ceramic tiles [32], ceramic blocks or electrical insulators [35]. Against this background, manufacturers of ceramic accessories have a significantly difficult process and implementation industry related to a large range of products produced in small production batches that often change in terms of volume, where the critical point determining the effectiveness of the entire process is the forming stage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, entrepreneurs need appropriate knowledge for the solutions they implement to bring the expected results. Each industry is characterized by individual conditions in terms of production technology, organization and work techniques [17,18,19,20]. It is practically impossible to develop a uniform improvement methodology for all production companies.…”
Section: Lean Manufacturingmentioning
confidence: 99%
“…There are many cases where the improvement rate is much more significant, but it seems that these cases are not as often. These findings are based on the research of other authors such as [57][58][59][60][61][62][63][64][65][66][67][68]. Based on a comparison of the classical indicators, the change achieved in the process is slightly above average.…”
Section: Discussionmentioning
confidence: 90%
“…The methodology has a set of tools, as shown on the left side of the schema in Figure 4 , and a “discrete event” utilization strategy and documents, as shown on the right side of the same schema. The aim of the methodology tools is to be the knowledge capture base, which is oriented towards long-term profitability based on “incremental” development in a comprehensive and continuous improvement way [ 41 ]. The discrete event strategy and documents are defined to take maximum advantage of the methodology tools in every application loop, and to help to document the analysis, calculations, and decisions carried out in each event.…”
Section: Methodology Developmentmentioning
confidence: 99%